Plan de marketing estratégico para la panadería “Delicias lojanas” de la ciudad de Loja, período 2016-2021 - Loaiza Carrión, Alexandra Diocelina (2017)
The purpose of this study was to propose a strategic marketing plan for “Panadería Delicias Lojanas” in order to improve the business performance of it. inductive, deductive, analytical and statistical: To develop this goal, methods as applied. Similarly it resorted to the use of techniques for data collection such as: interview with Manager Delicias Bakery yojanas Mr. Wilfrido Vivanco, and the use of surveys to customers and 2 294 employees of the company. In the Results section, after the evaluation is to external factors of the company, the parent External Factors Evaluation EFE arises, the weighted result was 3.15, which is interpreted that the company is responding excellent opportunities to address existing threats in the sector way. Also in this section was indispensable evaluation of internal factors Delicias Bakery yojanas through the matrix Internal Factors Evaluation EFI, which gave as a result weighted 3.65 which means that holds significant predominance of strengths on weaknesses. With the internal-external matrix (IE) allowed establish that the Delicias Bakery yojanas should apply growth strategies for further consolidation and performance of it in the lojano market. Competitive profile matrix determined that when there is a significant level of competition in the sector or area for Delicias Bakery yojanas regarding the production and marketing of roscón Then the SWOT matrix was established based on the analysis of internal and external factors. Once they organized proceeded to build the matrix High Impact, which allowed to establish four strategic objectives as key for further growth of the Bakery Delicias yojanas: 1) Development of an annual plan of acquisition of raw material under exclusive contract with the supplier. 2) Development of an annual training plan staff Delicias Bakery yojanas. 3) design trademark and logo for product identification. 4) Development of a plan for Advertising and Promotion Delicias Bakery yojanas. With the establishment of the strategic objectives could be realized formulation or proposed Strategic Marketing Plan for Delicias Bakery yojanas. These strategic objectives are designed to promote marketing activities roulade with its budget amounts to the same as the amount of $ 3,844.80; which it is designed to realize it within one year.